Weekend effect in endovascular stroke treatment: do treatment decisions, procedural times, and outcome depend on time of admission?. (18th March 2016) - Nikoubashman, Omid; Probst, Thomas; Schürmann, Kolja; Othman, Ahmed E; Matz, Oliver; Brockmann, Marc-Alexander; Müller, Marguerite; Wiesmann, Martin; Reich, Arno
Abstract : Background: Epidemiologic studies identified a 'weekend effect' or 'out-of-hours effect', which implies that procedural and clinical outcomes of patients with stroke, who are admitted out-of-hours, are less favorable than for patients admitted during working-hours. Objective: To determine (1) whether our procedural times and clinical outcome were affected by an out-of-hours effect and (2) whether the decision in favor of, or against, endovascular stroke treatment (EST) depends on the time of admission. Methods: Between February 2010 and January 2015, 6412 consecutive patients presenting with symptoms of acute ischemic stroke were evaluated for EST eligibility according to established local protocols and generally accepted consensus criteria, and dichotomized into working-hours and out-of-hours cohorts according to admission times. Within both groups, patients given EST were identified and the rate of treatment decision, procedural times, and clinical outcome were compared and analyzed. Results: Clinical and radiological features of patients admitted in working-hours and out-of-hours did not differ significantly. Procedural times and clinical outcome were not affected by an out-of-hours effect (p≥0.054). 221/240 (92.1%) out-of-hours patients and 154/166 (92.8%) working-hours patients who were eligible for EST were transferred to the angiography suite for EST (p=0.798). The rationale not to treat patients who were eligible for EST did not differ between working-hours and out-of-hours admission (p=0.756). Conclusions: It is possible to produce competitive procedural times regardless of the time of admission and to prevent a treatment decision bias when standard operating procedures are applied consistently.